A Clinical Roadmap to Investigate the Genetic Basis of Pediatric Pheochromocytoma: Which Genes Should Physicians Think About? - Bernardo Dias Pereira; Tiago Nunes da Silva; Ana Teresa Bernardo; Rui César; Henrique Vara Luiz; Karel Pacak; Luísa Mota-Vieira (International Journal of Endocrinology)
Pheochromocytoma is very rare at a pediatric age, and when it is present, the probability of a causative genetic mutation is high. Due to high costs of genetic surveys and an increasing number of genes associated with pheochromocytoma, a sequential genetic analysis driven by clinical and biochemical phenotypes is advised. The published literature regarding the genetic landscape of pediatric pheochromocytoma is scarce, which may hinder the establishment of genotype-phenotype correlations and the selection of appropriate genetic testing at this population. In the present review, we focus on the clinical phenotypes of pediatric patients with pheochromocytoma in an attempt to contribute to an optimized genetic testing in this clinical context. We describe epidemiological data on the prevalence of pheochromocytoma susceptibility genes, including new genes that are expanding the genetic etiology of this neuroendocrine tumor in pediatric patients. The clinical phenotypes associated with a higher pretest probability for hereditary pheochromocytoma are presented, focusing on differences between pediatric and adult patients. We also describe new syndromes, as well as rates of malignancy and multifocal disease associated with these syndromes and pheochromocytoma susceptibility genes published more recently. Finally, we discuss new tools for genetic screening of patients with pheochromocytoma, with an emphasis on its applicability in a pediatric population.